1992
DOI: 10.1172/jci115623
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus-stimulated peripheral blood mononuclear cells induce HIV-1 replication via a tumor necrosis factor-alpha-mediated mechanism.

Abstract: Human cytomegalovirus (HCMV) is a potential cofactor in HIV-1 infection. To investigate the mechanism whereby HCMV promotes HIV-1 replication, a PBMC coculture assay which measures HIV-1 p24 antigen release was used as an index ofviral replication. HCMV-stimulated PBMC were capable of inducing HIV-1 replication in cocultures with acutely infected PBMC; however, this occurred only when the PBMC were from HCMV-seropositive donors (598±207 versus 27±10 pg/ml p24 antigen with PBMC from HCMV-seronegative donors on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
1

Year Published

1993
1993
2001
2001

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 46 publications
(34 reference statements)
4
32
1
Order By: Relevance
“…The inhibition was reversed to approximately control levels when MO were grown in the presence of mAb to TNF-␣ (Table III). These findings are in agreement with others and support the concept that TNF-␣ is a key mediator in the pathogenesis of HCMV disease (18,35). TNF-␣ has been identified as an important factor in the pathogenesis of AIDS.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The inhibition was reversed to approximately control levels when MO were grown in the presence of mAb to TNF-␣ (Table III). These findings are in agreement with others and support the concept that TNF-␣ is a key mediator in the pathogenesis of HCMV disease (18,35). TNF-␣ has been identified as an important factor in the pathogenesis of AIDS.…”
Section: Discussionsupporting
confidence: 93%
“…CMV enhanced HIV replication in T cells and in mononuclear phagocytic cells (15)(16)(17). CMV-stimulated PBMC from CMV seropositive patients and enhanced HIV replication when co-cultured with acutely infected PBMC (18). The enhancement of HIV replication was associated with the release of TNF-␣ from the CMV stimulated PBMC.…”
Section: Cytomegalovirus (Cmv)mentioning
confidence: 89%
See 1 more Smart Citation
“…TNF-x production by these cells might be influenced by coinfection with other viruses or bacteria. It has been reported that human eytomegalovirus-stimulatcd PBMC could induce HlV-1 rephcation via a TNF-x-mediated mechanism [52]. and for alveolar macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…A CMV infection is normally subclinical but can be fatal in immunocompromised individuals or if the infection is acquired in utero. The cytokine profile of the early phase of CMV infection is typically proinflammatory, with production of IL-1␤, IL-6, IL-12, TNF-␣, IFN-␣/␤, and IFN-␥ (38,183,192,235,266). One of the major components of the CMV virion is the glycoprotein gB, and studies have shown that a significant proportion of the virus-host interactions are mediated through gB (27,267).…”
Section: Cytomegalovirusmentioning
confidence: 99%